2016
DOI: 10.1063/1.4960253
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of low-dimensional alumina structures

Abstract: Abstract. Nano-dimensional materials have recently attracted much attention with respect to their potential role in medicine. Physical mechanisms of interaction of nanoparticles with tumor cells will help to develop new methods for cancer disease treatment. Based on aluminum oxide phases, positively charged low-dimensional structures have different shape: agglomerates of nanosheets, nameplates, cone-shaped nanoaggregates were synthesized with the help of aluminum nanoparticles. The cytotoxicity effect of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The nanoparticles' shape and structure contribute to reducing the attraction forces between particles. As shown in [24,35], AlO(OH) nanoparticles after hydrolysis are characterized by a complex structure with needle branches, which leads to a high binding energy between nanoparticles and high fractions of particles with larger sizes. In contrast, the ZnO nanoparticles have geometric shapes (hexagon, circle, square, rectangle) (Figure 2a), which can reduce particle agglomeration.…”
Section: Morphology Of the C-p Coatingsmentioning
confidence: 99%
“…The nanoparticles' shape and structure contribute to reducing the attraction forces between particles. As shown in [24,35], AlO(OH) nanoparticles after hydrolysis are characterized by a complex structure with needle branches, which leads to a high binding energy between nanoparticles and high fractions of particles with larger sizes. In contrast, the ZnO nanoparticles have geometric shapes (hexagon, circle, square, rectangle) (Figure 2a), which can reduce particle agglomeration.…”
Section: Morphology Of the C-p Coatingsmentioning
confidence: 99%
“…Recently it has been experimentally found that the low-dimensional aluminum oxyhydroxide is prospective nanomaterial (AlOOH-NM), at least, to be adjuvant in anticancer therapy [9,10]. The mechanism of AlOOH-NM antitumor activity may be provided by the oxyhydroxide influence on pH of extracellular media [11,12] or/and by probable violations in the cell membrane structure accompanied by membrane protein dysfunction, as well as by facilitating cellular uptake of the therapeutic agents, or something fourth.…”
Section: Introductionmentioning
confidence: 99%